Pengembangan Soal Serupa TIMSS untuk Mengukur Kemampuan Berpikir Kritis dan Pemecahan Masalah pada Konten Aljabar Kelas VIII - Hapsari, Oktavia; , Prof.Dr.Budi Murtiyasa, M.Kom (2016)
International institutions such as the Trends in International Mathematics and Science Study (TIMSS) put Indonesia on a position that has not been encouraging. This is because Indonesia is still experiencing difficulties in dealing with mathematical problems, especially maths models TIMSS. This research aims to develop a similar problem TIMSS on algebra content to measure the ability of critical thinking and problem solving are valid and practical. The method used in this research is the development of research methods. The study consisted of two stages: preliminary and formative stages of evaluation that includes self evaluation, expert reviews and one-to-one, small group and field test. Data collection techniques used walk-throughs, document, test and interview. After going through the one-to-one or small group, about tested at the stage of field tests in class VIII B of SMP Negeri 1 Colomadu. The test results overall with an average value of critical thinking skills of 72, included in the category of good critical thinking skills. However, these results can also be said that a similar problem developed TIMSS considered valid and practical criteria and have a potential effect on students' critical thinking. Keywords: critical thinking ability, TIMSS, problem solving, Algebra.